Comparative Screening analysis of Natural metabolites against a cholera toxin - R. Balajee and M.S.Dhana Rajan (Journal of Applied Pharmaceutical Science, 2013)
Cholera is one of the earliest infections to be studied by epidemiological methods. Worldwide it affects 3-5 million people and causes 100,000-130,000 deaths a year as of 2010. Cholera is an infection of the small intestine that causes a large amount of watery diarrhea; it is caused by the bacterium vibrio cholerae. The cholera toxin (CTX or CT) is an oligomeric complex made up of six protein subunits a copy of A subunit and the five copies of B subunit, connected by a disulfide bond. This study is based on targeting the CTX using computational tools, a natural metabolite mangiferin was taken and its chemical features are generated using common pharmacophore analysis, using minmaybridge database and taken lead compound were optimized and the Lipinski’s Rule of 5 properties were analyzed. Here, the binding affinity of protein – ligand interaction studied and displayed using ligand fit.
Keywords: Cholera, CTX, Mangiferin, pharmacophore, similar com